Regulation of sphingolipid metabolism in the immune microenvironment of gastric cancer: current insights and future directions - Hua, Yunqi; Zhang, Gangling; Liu, Yubo; Tian, Xiaoling; Zhang, Xinyi; Song, Ge; Tian, Qinggang; Yin, Fangrui (Frontiers in Oncology, 2025)
In recent years, the role of sphingolipid metabolism in the tumor immune microenvironment has gradually gained attention, particularly in gastric cancer research. Sphingolipids are crucial components of cell membranes that regulate cell signaling and immune responses, making them important in tumor biology research. Despite numerous studies exploring the relationship between sphingolipid metabolism and gastric cancer, the specific regulatory mechanisms remain unclear. Further investigation is needed to understand their roles in the immune microenvironment. This article aims to review the regulatory mechanisms of sphingolipid metabolism in the immune microenvironment of gastric cancer, discussing its potential applications in tumor occurrence, development, and treatment. By analyzing current research progress, we will clarify the complex relationship between sphingolipid metabolism and immune cell interactions and look forward to future research directions, hoping to provide new ideas and strategies for immunotherapy in gastric cancer.